The Influence of the Application of Constructivism Philosophy on Elementary School Students’ Learning Independence - Nina Anis; Aiman Fariq; Alal Chahine (International Journal of Educational Narratives, 2025)
Background. This study aims to examine the influence of constructivism philosophy application on elementary school students’ learning independence. The rapid changes in educational paradigms emphasize the need for students to actively engage in their learning processes. Constructivism, with its focus on learners building knowledge through experience and reflection, has been identified as a potential catalyst in fostering students’ independence. Purpose. The objective of this research is to determine how the implementation of constructivist-based learning strategies can impact students’ ability to work autonomously in the learning environment. This research adopts a quasi-experimental method with a pre-test and post-test design. Method. The sample consists of two groups of elementary school students, with one group receiving constructivist-based instruction and the other group following traditional teaching methods. Data collection involved observation, questionnaires, and tests to measure the level of students’ learning independence before and after the intervention. Results. The results revealed that the application of constructivist principles significantly improved students’ learning independence, as seen from the increased scores in the post-test and positive feedback from observational data. Conclusion. This study concludes that constructivist-based learning can effectively enhance students’ independence, suggesting that educators should consider incorporating these strategies into their teaching practices.